2013
DOI: 10.1371/journal.pone.0058911
|View full text |Cite
|
Sign up to set email alerts
|

Brap2 Regulates Temporal Control of NF-κB Localization Mediated by Inflammatory Response

Abstract: Nuclear factor-kappaB (NF-κB) is critical for the expression of multiple genes involved in inflammatory responses and cellular survival. NF-κB is normally sequestered in the cytoplasm through interaction with an inhibitor of NF-κB (IκB), but inflammatory stimulation induces proteasomal degradation of IκB, followed by NF-κB nuclear translocation. The degradation of IκB is mediated by a SCF (Skp1-Cullin1-F-box protein)-type ubiquitin ligase complex that is post-translationaly modified by a ubiquitin-like molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…As its neddylation status was not investigated in this latter study, the exact functions of BCA3 and the role of its neddylation in NF-κB regulation merit further investigation under physiological conditions. In a final study, the RING E3 ubiquitin ligase BRAP2, which has several reported functions in intracellular signaling, was found both to interact with NEDD8 and to be neddylated, albeit solely by over-expression studies 141 . Interestingly, BRAP2 was neddylated on a lysine residue in a sequence stretch that is homologous to the NEDD8 consensus site in cullins.…”
Section: Neddylation In Transcriptional Regulationmentioning
confidence: 94%
See 1 more Smart Citation
“…As its neddylation status was not investigated in this latter study, the exact functions of BCA3 and the role of its neddylation in NF-κB regulation merit further investigation under physiological conditions. In a final study, the RING E3 ubiquitin ligase BRAP2, which has several reported functions in intracellular signaling, was found both to interact with NEDD8 and to be neddylated, albeit solely by over-expression studies 141 . Interestingly, BRAP2 was neddylated on a lysine residue in a sequence stretch that is homologous to the NEDD8 consensus site in cullins.…”
Section: Neddylation In Transcriptional Regulationmentioning
confidence: 94%
“…TNF stimulation leads to BRAP2 neddylation and suppression of NF-κB nuclear translocation. However, a link between the two effects is lacking and it is possible that the inhibition of NF-kB is rather mediated through interaction with CUL1 by a neddylation-independent mechanism 141 . Thus, further work is required to assess whether BRAP2 neddylation has a physiological significance and a function in NF-κB signaling.…”
Section: Neddylation In Transcriptional Regulationmentioning
confidence: 99%
“…BRAP2 was also identified as a NEDD8 interacting protein in a yeast two-hybrid screen and to also bind CUL1 within the Cul1 bTrcp complex that activates NFkB. Interestingly, BRAP2 is NEDDylated in a lysine that is within a motif similar to that of cullin NEDDylation (Takashima et al 2013). The role of NEDD8 in BRAP2 function is not clear.…”
Section: Nfkbmentioning
confidence: 99%
“…The role of NEDD8 in BRAP2 function is not clear. However, overexpression or knockdown of BRAP2 leads to inhibition of NFkB nuclear translocation and activation, suggesting that BRAP2-NEDDylation or other post-translational modifications may control BRAP2 complex formation with components of the NFkB pathway (Takashima et al 2013). Depending on cellular conditions NFkB can act as an oncogene or tumour suppressor (Perkins 2012).…”
Section: Nfkbmentioning
confidence: 99%
“…Differently from cullins that are neddylated on a single conserved lysine residue, all these novel substrates have been shown to be ubiquitinated as well as neddylated at multiple residues, which are in most cases overlapping. The only known exception is given by BRAP2 in which the neddylation site Lys432 is within an amino acid sequence that resembles the consensus neddylation sequence conserved in all cullin family proteins [72]. Consequently, while ubiquitination of these residues promotes the proteasomal degradation of target proteins, the addition of NEDD8 moieties to the same residues prevents substrate degradation.…”
Section: General Overviewmentioning
confidence: 99%